Plasma Levels of Amino Acids Related to Urea Cycle and Risk of Type 2 Diabetes Mellitus in Chinese Adults - Cao, Yun-Feng; Li, Jing; Zhang, Zhipeng; Liu, Jinnan; Sun, Xiao-Yu; Feng, Xiao-Fei; Luo, Hui-Huan; Yang, Wen; Li, Sai-Nan; Yang, Xilin; Fang, Zhong-Ze (Frontiers in Endocrinology, 2019)
Objective: This study aimed to test associations between type 2 diabetes mellitus (T2DM) and metabolites in urea cycle including arginine, citrulline and ornithine. Methods:This study used a hospital-based cross-sectional study design. We retrieved medical notes of 401 in-patients with onset of T2DM within 2 years and 1,522 healthy subjects who attended annual physical examination. All cases were admitted to a tertiary care center in Jinzhou, China from May 2015 to August 2016. Binary logistic regression analyses were performed to obtain odds ratios (ORs) and 95% confidence intervals (CIs). Results:Patients with T2DM had higher arginine, and lower ornithine than control subjects. Levels of citrulline were similar in two groups. Arginine was positively associated with T2DM (ORs: 1.20, 1.17–1.23) while ornithine was negatively associated with T2DM (OR: 0.89, 0.88–0.91). After adjustment for other amino acids and traditional risk factors, these associations were still significant and persistent for arginine and ornithine. The association between citrulline and T2DM was not significant. Their ratios of pairs of two amino acids were associated with increased risk of T2DM. After adjustment for other ratios of amino acids, effect size for T2DM remained significant. Further adjustment for traditional risk factors did not lead to large changes (ORs: 1.78, 1.20–2.65 for the ratio of arginine to ornithine; ORs: 1.59, 1.37–1.86 for the ratio of citrulline to ornithine, respectively) except the ratio of arginine to citrulline. Conclusions: Plasma levels of amino acids related to urea cycle and their ratios of these amino-acids were associated with T2DM in Chinese adults.